WINCKELMANN AND CASANOVA IN ROME: A Case Study of Religion and Sexual Politics in Eighteenth-Century Rome - Ruprecht, Louis A. (Journal of religious ethics, 2010)
There are three “scandals” that appear in most discussions of Johann Joachim Winckelmann (1717–1768), the so-called father of modern Art History: his allegedly careerist conversion to Catholicism in 1754; his semi-secret homoerotic discourse while under Vatican employ in the early-to-mid 1760s; and his shocking murder in Trieste in 1768. Of the three, Winckelmann's sexuality has garnered the most attention in recent scholarship. A little-known story reported by Casanova during his second visit to Rome in 1761 has something to do with that. In this essay, I argue that we make too much of sexuality these days and, in so doing, fail to register the far more radical religious activities in which Winckelmann was involved, most notably the creation and curation of the Vatican Museums, with their almost casual display of naked statues of pagan divinities. Winckelmann's “profanity,” not his sexuality, constitutes the revolutionary core of his life's work and enduring influence. The statues he discussed so passionately were not simply naked; they were pagan.